Perspektywy rozwoju gospodarki turystycznej opartej na wiedzy w regionie na przykładzie województwa dolnośląskiego - Nawrocka, Elżbieta (Perspectives for Development of Knowledge-Intensive Tourism Economy Based on the Example of Lower Silesia Region, 2008)
The objective of the hereby article is to analyze and evaluate the process of knowledge-intensive tourism economy development in Lower Silesia region. The diagnosis has been conducted basing on the model of knowledge-intensive economy and constructed on the basis of World Bank and OECD documents. The basic pillars of knowledge-intensive tourist economy in the region are: innovation system, education system and improvements in tourist oriented education system, information and communication system, knowledge management at the level of tourist enterprises, knowledge and information management at local and regional level, as well as institutional and business environment. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 81-91